An Examination of Memory Performance in a Fearful Virtual Reality Gaming Context. (June 2023) - Lo, L. Y.; Ip, C. L.
Background: The emotion of fear bears a survival significance enabling animals to be highly vigilant in contexts of uncertainty. Expectedly, not all information available in the environment can be processed. Given that a major goal is to get rid of the source of fear in a fearful situation, the current study therefore hypothesized that information relating to the fear source would be better attended to and recalled than contextual information, which was validated by comparing participants' recall of different types of information presented in a fearful VR gaming context. Methodology: Fifty-four participants were divided into two groups and finished a specific segment of a VR game with different fear levels. Results: No significant difference in recall performance on the questions about the appearance of the fear source and the questions about the interaction with the source was observed between the fear and less-fear groups. Yet, contextual information was better recalled than information related to the fear source in both groups. Regardless of whether the contextual information was provided beforehand or not, participants still tended to focus primarily on the environment in the gameplay. Also, the immersiveness of the gameplay was positively related to participants' fear level. Discussion: The tendency of attending to contextual information was speculated to be unconditional, in line with the risk calculation observed in prey when situated in less familiar contexts. It was suggested to further validate the present primarily findings by adopting VR headset with eye-tracking function in future studies. Lastly, an understanding of fear's effect on memorization might also provide some information for developing future survival horror games.